Colonization of Germ-Free Piglets with Commensal Lactobacillus amylovorus, Lactobacillus mucosae, and Probiotic E. coli Nissle 1917 and Their Interference with Salmonella Typhimurium - Splichal, Igor; Donovan, Sharon M; Splichalova, Zdislava; Neuzil Bunesova, Vera; Vlkova, Eva; Jenistova, Vera; Killer, Jiri; Svejstil, Roman; Skrivanova, Eva; Splichalova, Alla (Microorganisms, 2019)
Non-typhoid Salmonellae are worldwide spread food-borne pathogens that cause diarrhea in humans and animals. Their multi-drug resistances require alternative ways to combat this enteric pathogen. Mono-colonization of a gnotobiotic piglet gastrointestinal tract with commensal lactobacilli Lactobacillus amylovorus and Lactobacillus mucosae and with probiotic E. coli Nissle 1917 and their interference with S. Typhimurium infection was compared. The impact of bacteria and possible protection against infection with Salmonella were evaluated by clinical signs, bacterial translocation, intestinal histology, mRNA expression of villin, claudin-1, claudin-2, and occludin in the ileum and colon, and local intestinal and systemic levels of inflammatory cytokines IL-8, TNF-α, and IL-10. Both lactobacilli colonized the gastrointestinal tract in approximately 100× lower density compare to E. coli Nissle and S. Typhimurium. Neither L. amylovorus nor L. mucosae suppressed the inflammatory reaction caused by the 24 h infection with S. Typhimurium. In contrast, probiotic E. coli Nissle 1917 was able to suppress clinical signs, histopathological changes, the transcriptions of the proteins, and the inductions of the inflammatory cytokines. Future studies are needed to determine whether prebiotic support of the growth of lactobacilli and multistrain lactobacilli inoculum could show higher protective effects.